Effort To Preserve Ka Ga Nga Local Script, Rejang Tribe In Rejang Lebong Regency - Hudaidah; Tedi Rizki (Criksetra: Jurnal Pendidikan Sejarah, 2022)
This paper examines the local script of Ka Ga Nga and its conservation efforts in the Rejang Tribe of Rejang Lebong Regency. The issues that will be raised are how the development of the Ka Ga Nga script and how efforts to preserve it. The purpose of the study is to describe the development of the Ka Ga Nga script and its preservation efforts. In conducting the study, historical or historical research methods with anthropological and sociological approaches were used, where the research was carried out in Rejang Lebong, Bengkulu province. The results obtained that the Ka Ga Nga script is estimated to have developed rapidly in Southern Sumatra in the 16th to 17th centuries AD as part of the development of the pallawa and kawi scripts. The Ka Ga Nga script is related to the script in the land of Bugis. Currently, the Ka Ga Nga script has decreased spread among the Rejang Lebong community so that the government and local customary bodies continue to strive to preserve the Ka Ga Nga script. The Customary Deliberation Board made prepentive efforts, through the introduction of the Ka Ga Nga script to the naming of public facilities and roads and the inclusion of the local content of the Ka Ga Nga script in the curriculum of the Rejang Lebong Regency elementary school.